An application of network data envelopment analysis with fuzzy data for the performance evaluation in cargo sector. Issue 4 (9th July 2018) - Simsek, Berna; Tüysüz, Fatih
Abstract : Purpose: The purpose of this paper is to present a methodology which enables to measure and analyze the performance of sub-process and overall system of a cargo company. Design/methodology/approach: Network data envelopment analysis method with fuzzy data is used for performance measurement which considers the sub-process efficiency simultaneously together with the overall efficiency and also the uncertainty included in input–output data. Findings: A real-life application of the proposed model is presented for Turkey. The application results show the efficiency scores of ten branches according to each sub-process and also the overall system. Although the obtained results are case specific, the application results indicate that the inefficient branches can achieve efficiency either by decreasing circulation ratio input for human resources sub-process or by increasing closed complaint output or by decreasing open complaint output for customer relationship management sub-process. Originality/value: The study presented provides insights into the performance measurement applications in cargo sector. The methodology presented provides the flexibility of removing or adding some new sub-processes and also decision-making units which enables the approach to be used for other performance evaluation problems.